2018
DOI: 10.31234/osf.io/yaevr
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social Decoys: Leveraging Choice Architecture to Alter Social Preferences

Abstract: Many of society's most significant social decisions are made over sets of individuals: for example, evaluating a collection of job candidates when making a hiring decision. Rational theories of choice dictate that decision makers' preferences between any two options should remain the same irrespective of the number or quality of other options. Yet people's preferences for each option in a choice set shift in predictable ways as function of the available alternatives. These violations are well documented in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
(40 reference statements)
2
4
0
Order By: Relevance
“…The present results suggest that part of the power of these interventions is in making errors more evenly distributed in judgment contexts (i.e., reducing bias). Finally, our results align with a more recent investigation finding that discrimination can be lessened by simply increasing the accuracy of the decision-making process (Chang & Cikara, 2018). At the same time, the present work extends these prior investigations by illustrating how warnings about potential bias can lead to reductions in the relative likelihood of certain groups receiving favorable treatment without influencing the amount of people receiving unfair treatment.…”
Section: Discussionsupporting
confidence: 89%
“…The present results suggest that part of the power of these interventions is in making errors more evenly distributed in judgment contexts (i.e., reducing bias). Finally, our results align with a more recent investigation finding that discrimination can be lessened by simply increasing the accuracy of the decision-making process (Chang & Cikara, 2018). At the same time, the present work extends these prior investigations by illustrating how warnings about potential bias can lead to reductions in the relative likelihood of certain groups receiving favorable treatment without influencing the amount of people receiving unfair treatment.…”
Section: Discussionsupporting
confidence: 89%
“…More recently we have documented similar preference shifts in social contexts (e.g., Chang, Gershman, & Cikara, 2019). For example, in the context of a hiring decision, we have demonstrated that participants had systematically different preferences for the exact same candidate as a function of the other candidates in the choice set and the salience of the candidate attributes under consideration (Chang & Cikara, 2018). The same logic applies to collective-level inferences-how favorably I feel toward collective A depends not only on my estimates of how likely A is coordinate with my collective, but also how likely B, C, and D are to coordinate with us (and one another) as well.…”
Section: New Insights From a Coalitional Perspective: Social Group Reference Dependencesupporting
confidence: 53%
“…Rather than marking a defect in human decision-making machinery, recent frameworks suggest that these 'violations' arise from a selective integration mechanism which ultimately leads to better decisions given the noise intrinsic to information processing (Howes, Warren, Farmer, El-Deredy, & Lewis 2016;Tsetsos et al, 2016). Though this phenomenon has been documented widely in consumer behavior contexts (e.g., Huber et al, 1982;Louie et al, 2013;Simonson, 1989), those studies that have examined context-dependence in the social domain have focused almost exclusively on a highly constrained choice set: one in which two options represent perfect tradeoffs on two attributes in the presence of a "decoy," which also has a very specific attribute profile (Chang & Cikara 2018;Herne, 1997;Highhouse, 1996;Pan et al, 1995, Pettibone & Wedell, 2000Sedikides, Ariely, & Olsen, 1999; with one exception: Furl, 2016). Of course, social choice sets very rarely conform to these parameters.…”
mentioning
confidence: 99%